2
$\begingroup$

I was reading a textbook and I encountered this question. I was wondering why we don't consider $M^\dagger$ instead of $M^{T}$, so I didn't show this relation, could you please help me to show below relation?

Let $M: \mathcal{H}^{\tilde{A}} \rightarrow \mathcal{H}^{B}$ be a linear map and denote its transpose map by $M^{T}: \mathcal{H}^{\tilde{B}} \rightarrow \mathcal{H}^{A}$. Show that $$ I \otimes M\left|\phi_{+}^{A \tilde{A}}\right\rangle=M^{T} \otimes I\left|\phi_{+}^{\tilde{B} B}\right\rangle $$ where $\left|\phi_{+}^{\tilde{A} A}\right\rangle:=\sum_{y=1}^{|A|}|y y\rangle^{\tilde{A} A}$ and $\left|\phi_{+}^{\tilde{B} B}\right\rangle:=\sum_{y=1}^{|B|}|y y\rangle^{\tilde{B} B}$ and these are maximally entangled states.

$\endgroup$
2
$\begingroup$

Both states live in $ H_A \otimes H_B $. We will compute their inner product with the basis states $ |i \rangle_A | j \rangle_B $ and show that they are equal. Indeed:

  • $$ \big(I \otimes M\big) |\phi_+^{AA} \rangle = \sum_{y=1}^{|A|} |y \rangle_A M|y\rangle_A \implies \\ \langle i|_A \langle j|_B \big(I \otimes M\big) |\phi_+^{AA} \rangle = \sum_{y=1}^{|A|}\langle i|y \rangle_A \langle j|_BM|y\rangle_A = \langle j|_BM|i\rangle_A = M_{ji} $$

  • $$ \big(M^T \otimes I\big) |\phi_+^{BB} \rangle = \sum_{y=1}^{|B|} M^T|y \rangle_B |y\rangle_B \implies \\ \langle i|_A \langle j|_B \big(M^T \otimes I\big) |\phi_+^{BB} \rangle = \sum_{y=1}^{|B|}\langle i|_A M^T |y\rangle_B \langle j|y \rangle_B = \langle i|_A M^T |j\rangle_B = \big(M^T\big)_{ij} = M_{ji} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.